2023
DOI: 10.1002/sia.7190
|View full text |Cite
|
Sign up to set email alerts
|

A mechanochemically created durable dynamic superhydrophilic‐like surface

Abstract: Superhydrophilicity (superwettability) is generally defined as either a static water contact angle near 0° or water completely wetting the surface. Here, we show that there is a superhydrophilic‐like surface that has a large static water contact angle but demonstrates superhydrophilicity in its dynamic water contact performance. We found that polyethylene terephthalate (PET) surfaces showed such behavior following mechanical abrasion with sandpaper. We have evaluated the wettability of the abraded PET surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As shown in figures 10(a) and (b), the major elements on the surface of untreated and only abraded PET samples are C and O. The main difference is only in the relative concentration of the elements (table S2 in the supplementary materials), and the peak ratios are different [48]. Figure 10 [44][45][46][47].…”
Section: Chemical Compositions Of Untreated and Treated Petmentioning
confidence: 98%
“…As shown in figures 10(a) and (b), the major elements on the surface of untreated and only abraded PET samples are C and O. The main difference is only in the relative concentration of the elements (table S2 in the supplementary materials), and the peak ratios are different [48]. Figure 10 [44][45][46][47].…”
Section: Chemical Compositions Of Untreated and Treated Petmentioning
confidence: 98%
“…[29] This reduction in surface tension leads to a WCA of 5-10°or allows for the complete absorption of water across the substrate's surface. [30] The -NH functional groups on the membrane surface, facilitated by the presence of the PPy particles, contribute to the formation of hydrogen bonds with water molecules, effectively entrapping them. Furthermore, previous research on the topic has demonstrated that increasing the pore size of a material, including electrospun membranes, can enhance its hydrophilicity and vice versa.…”
Section: Superhydrophilic Behavior Of the Ppy-decorated Electrospun M...mentioning
confidence: 99%